Identification Of Mangrove Vegetation In South Segoro Anak, National Sanctuary Of Alas Purwo, Banyuwangi, East Java - Mustofa Niti Supardjo (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2008)
Selection of systematic sampling at South Segoro Anak areas as vast as 4 % of mangrove vast, following the direction of pilot line from Block of PAL to Block of Randu. The parameters observed is diamater of pillar/tree highly 1.3 meters, amount pillar/tree, weaned and seedling at every plots and plant type of mangrove existing in a plot. This research is made on 16 April-28 June 2006. Result of vegetation analysis with systematic sampling method at pillar level, weaned and seedling be obtained type of mangrove they are : Avicennia alba, Avicennia lanata, Avicennia marina, Avicennia officinalis, Bruguiera gymnorrhyza, Ceriops decandra, Ceriops tagal, Excoecaria agallocha, Lumnitzera racemosa, Rhizophora mucronata, Rhizophora apiculata, Schypiphora hydrophyllacea, Sonneratia alba, Sonneratia caseolaris, Xylocarpus granatum, Xylocarpus molluccennis, Heritiera littoralis. They are forms regular or uniform distribution pattern. Calculation of Morishita index at plant of mangrove in South Segoro Anak, Alas Purwo National Park of Banyuwangi-East Java can be described that is spreading pattern is regular, because value of IS which less than 1 (one). The regular or uniform spreading is reflecting the existence of negative individual interaction, like emulation to obtaining space, nutrition and sunlight.  Keywords: Identification, vegetation, mangrove, South Segoro Anak